2012
DOI: 10.1051/0004-6361/201219749
|View full text |Cite
|
Sign up to set email alerts
|

Influence of collisional rate coefficients on water vapour excitation

Abstract: Context. Water is a key molecule in many astrophysical studies that deal with star or planet forming regions, evolved stars, and galaxies. Its high dipole moment makes this molecule subthermally populated under the typical conditions of most astrophysical objects. This motivated calculation of various sets of collisional rate coefficients (CRC) for H 2 O (with He or H 2 ), which are needed to model its rotational excitation and line emission. Aims. The most accurate set of CRC are the quantum rates that involv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…The averaged excitation temperature is calculated by taking into account the regions of the cloud that contribute to the emerging line profile, the average being given by Eq. ( 2) of Daniel et al (2012).…”
Section: Molecular Excitation Modelingmentioning
confidence: 99%
“…The averaged excitation temperature is calculated by taking into account the regions of the cloud that contribute to the emerging line profile, the average being given by Eq. ( 2) of Daniel et al (2012).…”
Section: Molecular Excitation Modelingmentioning
confidence: 99%
“…Recently, Dubernet et al (2009) and Daniel et al (2011) published new H 2 O-H 2 collisional rates. Daniel et al (2012) compared these collision rates to those from Faure et al (2007) and found that the line strengths can be affected by up to a factor of 3 for low H 2 O abundance (n H 2 O /n H 2 ∼ 10 −8 ) and low density (n H 2 < 10 7 ) regimes. They also note that when H 2 O excitation is dominated by pumping via the dust radiation field, these differences are attenuated.…”
Section: The Model Gridmentioning
confidence: 99%
“…They change within a factor two, while all other high excitation lines stay within 10%. A possible explanation is that the high excitation lines originate close to the inner rim of the outer disk, where the dust temperature is higher (70−110 K) and the level populations could be dominated by IR pumping (Daniel et al 2012). A possibility to quantify this radiative pumping is to compare the excitation temperature of a lines upper level T ex with the temperature of the radiation field at that wavelength T rad and the local gas temperature T gas .…”
Section: The Statistical Equilibrium and Line Transfer Of Watermentioning
confidence: 99%